Hot rolled alloy steel wire rod for pre-stressed steel - Specification - Maleque, Md. Abdul (DSM, 2017)
This Malaysian Standard specifies the requirements for hot-rolled steel wire rods for pre-stressing steel bar concrete. This standard is applicable for the manufacture of hot rolled steel wire rods for pre-stressing steel bar concrete (hereinafter referred to as wire rod).